2014
DOI: 10.1080/03650340.2014.892584
|View full text |Cite
|
Sign up to set email alerts
|

Improving chilling tolerance of rice seedling by seed priming with salicylic acid

Abstract: This study was carried out in the Seed Research Laboratory of the Department of Crop Science, Ferdowsi University of Mashhad, Iran, in summer 2011. Rice (cv. Khazar) seeds were soaked in 0, 20, 50, and 100 mg l −1 salicylic acid (SA) aerated solutions for 24 h and then dried back to original moisture content and were sown in three temperatures (28°C as normal and 12°C and 8°C as chilling temperature conditions). In the first step, both treated and untreated seeds were sown at the optimum temperature (28°C). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…In rice, priming with 5-aminolevulinic acid improved shoot elongation [81] while priming with picomolar rutin augmented both root and shoot length in relation to an increase in photosynthetic pigments, phenolic and flavonoid contents [82]. In wheat, priming with sodium prusside stimulated plant growth as a consequence of improved capacity to scavenge free radicals by antioxidants [83], and a similar observation was reported for rice as a result of an increase in glutathione peroxidase (GPX) activity [24] and other antioxidant enzyme activities [84].…”
Section: Plant Growthmentioning
confidence: 70%
See 1 more Smart Citation
“…In rice, priming with 5-aminolevulinic acid improved shoot elongation [81] while priming with picomolar rutin augmented both root and shoot length in relation to an increase in photosynthetic pigments, phenolic and flavonoid contents [82]. In wheat, priming with sodium prusside stimulated plant growth as a consequence of improved capacity to scavenge free radicals by antioxidants [83], and a similar observation was reported for rice as a result of an increase in glutathione peroxidase (GPX) activity [24] and other antioxidant enzyme activities [84].…”
Section: Plant Growthmentioning
confidence: 70%
“…Frequently, such improvement is obvious just after emergence at the seedling level, but progressively disappears at the adult stage. For example, some young plants issued from priming treatments displayed improvement of resistance to chilling [84], low temperature [75], salinity [43,102], high temperature [80], drought [24,65,103], and UV exposure [82]. Some interesting studies also demonstrated that priming may afford resistance to biotic stresses such as Fusarium oxysporum in tomato [104], viral disease in Brassica rapa [105], and downy mildew in pearl millet [106].…”
Section: Stress Resistancementioning
confidence: 99%
“…The improved germination characteristics are attributed to the activation of priming-induced metabolic activities, referred to as "priming memory", including de novo synthesis of nucleic acids and proteins, ATP production, restoration of antioxidant activities, and cellular repair [11]. Previous studies about seed priming mainly focused on its benefits, involving germination features, antioxidant process, cell cycle and cell structures, and expression of genes and proteins, against various abiotic stresses including drought, heavy metals, and chilling [10,12,13]. Very few researches have payed attention to the effects of artificially aging and subsequent priming, but only at germination and seedling growth, antioxidant enzymes' activities, and seed reservoirs in species, such as cucumber (Cucumis sativa L.) [14] and maize (Zea maize L.) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, primed plants show faster and/or stronger activation of defence responses when subsequently challenged by abiotic/biotic stress, and this is frequently linked to development of local and systemic immunity and stress tolerance (Conrath, ; Islam et al , ). Previously, seed priming with SA was applied to improve seedling growth and the antioxidant defence system in sweet sorghum under high temperature and salinity (Nimir et al , ), as well as chilling tolerance in rice seedlings (Pouramir‐Dashtmian et al , ). In addition, seed treatment with SA resulted in decreased charcoal rot disease caused by fungi in sunflowers (Al‐Wakeel et al , ).…”
Section: Introductionmentioning
confidence: 99%